Measuring Home Activities and Participation of Children Receiving Early Childhood Intervention Services in Spain - Morales-Murillo, Catalina Patricia; Pacheco-Molero, Manuel; León-Estrada, Irene; Fernández-Valero, Rosa; Gutiérrez Ortega, Mónica; McWilliam, R. A. (Early Childhood Education Journal, 2024)
This study analyzed the fit of data collected with the Measure of Engagement, Independence, and Social Relationships for 3- to 5-year-olds (MEISR 3-to-5-years-old) to a proposed theoretical model based on the cross-walk of MEISR 3-to-5-years-old items and codes from 7 chapters of the Activities and Participation component of the International Classification of Functioning, Disability and Health-Children and Youth (ICF-CY). Participant children (N = 599) were recruited from 44 early childhood intervention programs across 9 autonomous communities (i.e., states) in Spain. Children’s ages ranged from 36 to 72 months (M = 49.22; SD = 9.77). Parents of children completed a sociodemographic questionnaire and a MEISR 3-to-5-years-old scale. Reliability and Confirmatory Factor Analysis (CFA) results supported the internal consistency of the MEISR 3-to-5-years-old items and its content validity for assessing child participation based on the ICF-CY framework. Statistically significant differences on the mean percentage of children who presented difficulties and learning opportunities when participating in home routines by the Activities and Participation ICF-CY chapters were found. No differences were found on children’s strengths for participation across chapters. Implications for practice are discussed. Such implications highlight the use of the MEISR 3-to-5-years-old in early childhood intervention programs to assess child functioning, plan interventions and follow-up child progress to promote learning and development of children.
Keywords: early intervention; ICF code set; child functioning; MEISR 3-to-5-years-old; activities and participation; validation